Frequência de aglutininas anti-Leptospira interrogans em equídeos de tração em Belo Horizonte, Minas Gerais, de agosto de 2001 a junho de 2008 - Cintia Ferreira (2009)
The current study evaluated anti-Leptospira interrogans aglutinine prevalence in draft horses, in nine regional administrative departments of Belo Horizonte city, in different times of the year. Samples were collected weekly in the Small Volume Reception Units (SVRUs), and distributed in the regional departments, since August 2001 until June 2008. Samples were processed by microscopic agglutination test (MAT), using icterohaemorrhagiae, copenhageni, canicola, pomona, ballum, brastilava, hardjo bovis and hardj serovars as antigens. The equidae were geographically referred in their departments to observe positive and negative distribution. The differences between sex, regional departments, months and years were analyzed by Chi-square test (X2), fixing the significance level in 95% (p<0,05). 3255 equidae serum were processed, in which 91,38% (2942/3255) were negative and 9,62% (313/3255) were positive. The most prevalent serovars were canicola (36,61%), hardjo bovis 23,83% and icterohamorrhagiae (16,71%). No difference (P>0,05) was observed among regional departments, however years and month studied showed significant difference (P<0,05).